Kualitas Bokasi dari Kotoran Berbagai Jenis Hewan - Irfan Irfan; Rasdiansyah Rasdiansyah; Mahlil Munadi (Jurnal Teknologi dan Industri Pertanian Indonesia, 2017)
Cow manure, different to other manures, has been frequently used as raw material of bokasi along with other organic waste materials such as sawdust, rice husk ash, and bran. This study aimed to utilize various livestock manures as one of the organic material in the production of bokasi. A completely randomized design with 2 replications was used in this study, which consisted of two factors: type of livestock manure (J) and proportion of livestock manure (P) of the total bokasi raw material.  Factor J consisted of 3 levels: J1 (cow manure), J2 (goats manure), and J3 (chicken manure), while factor P consisted of 4 levels: P1 (35%), P2 (45%), P3 (55%), and P4 (65%). Analysis of the bokasi quality included: total microorganisms, moisture content, pH, temperature, C element, N element N, C/N ratio, organoleptic  (texture, smell and color), and the plants growth (height) test. The results showed that the type of livestock manure (J) effected very significant on total microorganisms, C, N and C/N ratio of bokasi, as well as significant on plant height. Based on the results of the C, N and C/N ratio it was known that the best bokasi resulted by chicken manure. It met the standard of INS (Indonesian National Standard). The proportion of manure affected very significant on water content as well as significant on N and plant height.